Structures - Davis, John; Classroom Video (Bendigo, Victoria : Classroom Video, 1999)
This video provides a range of everyday examples of structures, both from nature & man made which help to clarify, in simple language, the principles underlying the properties of structures
Title from title screen
Editor & sound, Dominique Fusy
Keywords: Buildings